What Police Say about Crime Prevention Through Environmental Design Training in Two Jurisdictions (England/Wales and New South Wales, Australia). (9th April 2019) - Monchuk, Leanne; Clancey, Garner
Abstract: Crime Prevention Through Environmental Design (CPTED) aims to reduce crime and disorder through the design and manipulation of the built environment. Various professions and agencies practice CPTED. The police typically play an important role in the delivery of CPTED by assessing planning applications, identifying criminogenic design features, and offering remedial advice. As with other areas of policing, the training and professional development opportunities have received limited academic attention. This article reports on data collected from studies conducted in England and Wales and in New South Wales (Australia). A stratified sample of 30 Designing out Crime Officers from England and Wales and a convenience sample of 36 Crime Prevention Officers from New South Wales Police Force were interviewed and their views on CPTED training and development sought. It will be seen that this comparative analysis highlights similar concerns amongst those responsible for delivering CPTED, regardless of jurisdiction and professional background. Concerns related to the limited training and continued professional development opportunities that assist officers in undertaking the role and the level of confidence with which they feel able to advocate CPTED recommendations. This article briefly questions the utility of operational policing to do this role, but if they do, they need to be adequately resourced, which includes the provision of a dedicated training and continued professional development programme.